ANALISIS DINAMIKA EKSPOR DAN KEUNGGULAN KOMPARATIF MINYAK KELAPA SAWIT (CPO) DI INDONESIA (ANALYSIS OF EXPORT DYNAMICS AND COMPARATIVE ADVANTAGE OF INDONESIAN CRUDE PALM OIL) - ADANG AGUSTIAN; PROJOGO U. HADI (SOCA: Jurnal Sosial Ekonomi Pertanian)
Crude Palm Oil (CPO) has been one of important agricultural export commodities ofIndonesia, but it faces competition with product from other exporting counties as well astrade barriers from importing countries. This study aims to analyse changes in export andcomparative and competitive advantage as indicators of Indonesian palm oilcompetitiveness. By employing trend and DRCR (Domestic Resource Cost Ratio) and PCR(Private Cost Ratio) methods, it is concluded that : (1) Quantity and value of Indonesian palmoil export, especially CPO (Crude Palm Oil) during 1996-2001 increased respectively by19.91% and 1.52% per annum, namely from 1.67 million tons and US$ 0.83 billion in 1996 to4.90 million tons and US$ 1.08 billion in 2001; (2) Most Indonesian CPO was exported toIndia (17.90%), the Netherlands (14,29%) and China (7.14%); (3) Domestic distribution ofpalm oil was controlled by the government aimed at maintaining the balance between thefilling of the domestic demand and the foreign exchange creation; (4) Trade policy in somemajor importing countries remains protective, namely imposition of high tariff, quota andhealth issues; and (5) Oil palm farm in Indonesia has a comparative as well as competitiveadvantage indicated by the DRCR and PCR coefficients of less than unity. It is suggestedthat oil palm needs to be continuously developed in Indonesia while attempting in variousWTO forum for more opened and fairer trade of palm oil.